1994
DOI: 10.1159/000106702
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Phosphatidylserine, Pyritinol, and Cognitive Training in Alzheimer's Disease

Abstract: 70 patients with probable Alzheimer''s disease were randomly allocated to four groups: 17 patients received only social support, 18 cognitive training twice a week, in 17 cognitive training was combined with pyritinol 2 x 600 mg/day and in 18 cognitive training was combined with phosphatidylserine 2 x 200 mg/day. Treatment duration was 6 months. Before and after treatment, the patients underwent neuropsychological testing as well as measurement of the regional cerebral metabolic rate for glucose using positron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 34 publications
2
57
0
3
Order By: Relevance
“…Typically these were short trials of a few weeks or up to 3 mo active treatment duration with 18 F-FDG PET before and during treatment (20)(21)(22). Trials that were extended for at least 6 mo also showed evidence of disease progression by further reduction of glucose metabolism in association cortices (23)(24)(25)(26). However, these trials had not been designed to assess progression.…”
Section: Discussionmentioning
confidence: 99%
“…Typically these were short trials of a few weeks or up to 3 mo active treatment duration with 18 F-FDG PET before and during treatment (20)(21)(22). Trials that were extended for at least 6 mo also showed evidence of disease progression by further reduction of glucose metabolism in association cortices (23)(24)(25)(26). However, these trials had not been designed to assess progression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, other experiments have shown an improvement in memory, learning capacity, and other cognitive parameters in PS-supplemented rodents [7][8][9][10][11]. This is plausible, since PS was found to stimulate neurotransmitter release [7,12], increase brain glucose metabolism [13,14] and reduce oxidative stress in the brain [15].In clinical studies, PS-containing preparations were found to selectively dampen stress levels [16][17][18], improve learning and perception parameters in children with attention deficit hyperactivity disorder (ADD) [19,20], and improve calculation speed of athletes [21]. Table 1 summarizes previously performed studies on PS and/or PA regarding brain function in the elderly.…”
mentioning
confidence: 87%
“…Sphingolipids and metabolites Reduction of the number of aberrant crypt foci and adenocarcinomas Dillehay et al [1994] Shift in tumor type (malignant → benign) Schmelz et al [1996; Symolon et al [2004]; Spitsberg [2005] Anticholesterolemic Noh & Koo [2003; Nyberg et al [2000]; Eckhardt et al [2002] Protection of the liver from fat-and cholesterolinduced steatosis Duivenvoorden et al 2006 Suppression of gastrointestinal pathogens Sprong et al [2002]; Vesper et al [1999]; Pfeuffer & Schrezenmeir [2001] Neonatal gut maturation Oshida et al [2003] Myelination of the developing central nervous system Oshida et al [2003] Endogenous modulators of vascular function Michel et al [2007] Associated with age-related diseases and the development of Alzheimer Parodi [2001]; Spitsberg [2005] Sphingosine 1-phosphate Mitogenic Zhang et al [1990Zhang et al [ , 1991 Phosphatidyl-serine (PS) Restore normal memory on a variety of tasks McDaniel et al [2003] Positive effects on alzheimer patients Crook et al [1992]; Heiss et al [1994]; Pepeu et al [1996]; Gindin et al [1998]; Hashioka et al [2004] Improve exercise capacity of exercising humans Kingsley [2006] Phosphatidylcholine (PC) Support liver recovery from toxic chemical attack or viral damage Kidd [2002] Protects the human GI mucosa against toxic attack Anand et al [1999] Reduction of necrotising enterocolitis Carlson et al [1998] Lysophosphat-idylcholine (lyso PC) Bacteriostatic and bactericidal capacity van Rensburg et al [1992] Strong gastroprotective role in the duodenal mucosa ; ; Kivinen et al [1995] Other components Vitamin E and carotenoids Antioxidants Spitsberg [2005] as a mediator of senescence in a cell culture...…”
Section: Polar Lipidsmentioning
confidence: 99%
“…Preliminary findings with humans, though, are limited [McDaniel et al, 2003]. At elevated doses of 200 mg per day, clinical trials with patients suffering from Alzheimer's disease showed positive effects [Crook et al, 1992;Gindin et al, 1998;Hashioka et al, 2004;Heiss et al, 1994;Pepeu et al, 1996]. PS supplementation on exercising humans showed that PS might alter neuroendocrine function and positively influenced perceived muscular soreness and well-being.…”
Section: Phospholipidsmentioning
confidence: 99%